Panels without borders witnessing trauma as human rights issues in graphic novels on the Israeli-Palestinian conflict - Loyola, Mary Kathleen B.; Villareal, Corazon D (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2015)
Trauma has typically been approached as an issue of psychology and memory. This perspective prves limited, however, in the face of the sweeping sociopolitical crises of recent years. This study investigates how selected graphic novels on the Israeli-Palestinian conflict use witnessing to frame instances of trauma as human rights issues that call for ethical engagement and sociopolitical response. It focuses on the sociopolitical dimension of trauma, arguing that the use of witness-figures and the act of bearing witness to trauma engenders a human rights-centric consciousness that activates and sustains meaningful response to traumatic incidents. The corpus for this study comprises the folowing graphic novels: Nahi al-Ali's A Child in Palestine, Guy Delisle's Jerusalem : Chronicles from the Holy City, Ari Folman's Waltz with Bashir, Sarah Glidden's How to Understand Israel in 60 Days or Less, Miriam Libicki's Jobnik!, and Joe Sacco's Palestine and Footnotes in Gaza. Through various visual and narrative strategies, these graphic novels carry out the four functions of bearing witness identified by Fuyuki Kurasawa : giving voice to rights violations; rendering these violations comprehensible to potential audiences; generating empathy for victims and witnesses of these violations; and memorializing these violations so as to prevent their recurrence. In doing so, these graphic novels do not only frame instances of trauma as human rights issues or cultivate audience engagement and response; they also construct ways of seeing and demonstrate modes of engagement that shape and galvanize potential responses to traumatic rights violations.
Thesis (B.A. in Comparative Literature)
Keywords: Psychic trauma in literature; Post-traumatic stress disorder in literature; Human rights in literature